Digital forensics with kali linux : perform data acquisition, data recover, network forensics, and malware analysis with Kali Linux 2019x - Parasram, Shiva V.N. (Birmingham, UK : Packt Publishing, Limited, 2020)
Kali Linux is a Linux-based distribution that's widely used for penetration testing and digital forensics. It has a wide range of tools to help for digital forensics investigations and incident response mechanisms. This updated second edition of Digital Forensics with Kali Linux covers the latest version of Kali Linux and The Sleuth Kit. You'll get to grips with modern techniques for analysis, extraction, and reporting using advanced tools such as FTK Imager, hex editor, and Axiom. Updated to cover digital forensics basics and advancements in the world of modern forensics, this book will also delve into the domain of operating systems. Progressing through the chapters, you'll explore various formats for file storage, including secret hiding places unseen by the end user or even the operating system.
Introduction to Digital Forensics -- Installing Kali Linux -- Understanding Filesystems and Storage Media -- Incident Response and Data Acquisition -- Evidence Acquisition and Preservation with dc3dd and Guymager -- File Recovery and Data Carving with foremost, Scalpel, and bulk_extractor -- Memory Forensics with Volatility -- Artifact Analysis -- Autopsy -- Analysis with Xplico -- Network Analysis.
Includes index.
Keywords: KALI LINUX